Forest vegetation on sacred sites of the Tangier Peninsula (NW Morocco) - discussed in a SW-Mediterranean context - Frosch, Birgit; Deil, Ulrich; Freiburg (Phytocoenologia, 2011)
Forest stands on sacred sites can document climax or preclimax vegetation. However, little is known about the potential climax character of sacred sites in Morocco. We studied the vegetation of Muslim sacred sites and graveyards in rural regions of the Tangier Peninsula in Northwest Morocco. Sacred sites were chosen according to a pre-stratified random sampling method, taking climatic and edaphic patterns into account. In tree stands of 68 sacred sites 140 phytosociological relevés were sampled and classified. In an attempt to evaluate their degree of preservation, the best preserved holy forests were compared with reference data of similar forest communities, recorded mainly on non-sacred sites in southern Spain and Portugal, and northern Morocco and Algeria. The forested vegetation of sacred sites shows a great variety. Abiotic factors, such as substrate and bioclimate, and human interventions (grazing, fire, a.o.) were found to be important differentiating factors. Besides well-conserved forests, a broad spectrum of degradation stages was documented. Most stands still shelter the original tree species combination, but vertical structure and floristic composition of the herb layer are strongly modified. Processes related to anthropo-zoogenic pressure, like therophytization, ruderalisation and overaging of the tree layer occur despite religious taboos. Near-natural holy forests belong to various subtypes of the Teucrio baetici-Quercetum suberis and the Rusco hypophylli-Quercetum cocciferae. In comparison to forests on non-sacred sites, these holy forests are very well preserved, as is indicated by the presence of strict forest species of the Quercetalia ilicis and the Querco-Oleion sylvestris, by transgressives of the Quercetalia pubescentis, and by a high constancy and abundance of ombro- and mesophilous taxa. Moreover, the comparison of phytosociological data from Morocco and Spain indicated an Ibero-Mauretanian distribution of several Quercus suber communities. In conclusion, sacred groves often seem to represent the potential natural vegetation. Exceptions are sacred groves with Wild Olive, which occur in an ecoregion where a thermomediterranean Quercus suber forest is considered to be the climax.
The following values have no corresponding Zotero field: pub-location: Stuttgart publisher: Schweizerbart'sche Verlagsbuchhandlung
Keywords: climax; degradation; Evergreen mediterranean forest; holy forest; maghreb; marabout; quercetea ilicis; sacred grove